Determinants of noninvasive ventilation success or failure in morbidly obese patients in acute respiratory failure. - Malcolm Lemyze (Public Library of Science (PLoS), 2014)
Purpose Acute respiratory failure (ARF) is a common life-threatening complication in morbidly obese patients with obesity hypoventilation syndrome (OHS). We aimed to identify the determinants of noninvasive ventilation (NIV) success or failure for this indication. Methods We prospectively included 76 consecutive patients with BMI>40 kg/m2 diagnosed with OHS and treated by NIV for ARF in a 15-bed ICU of a tertiary hospital. Results NIV failed to reverse ARF in only 13 patients. Factors associated with NIV failure included pneumonia (n = 12/13, 92% vs n = 9/63, 14%; p<0.0001), high SOFA (10 vs 5; p<0.0001) and SAPS2 score (63 vs 39; p<0.0001) at admission. These patients often experienced poor outcome despite early resort to endotracheal intubation (in-hospital mortality, 92.3% vs 17.5%; p<0.001). The only factor significantly associated with successful response to NIV was idiopathic decompensation of OHS (n = 30, 48% vs n = 0, 0%; p = 0.001). In the NIV success group (n = 63), 33 patients (53%) experienced a delayed response to NIV (with persistent hypercapnic acidosis during the first 6 hours). Conclusions Multiple organ failure and pneumonia were the main factors associated with NIV failure and death in morbidly obese patients in hypoxemic ARF. On the opposite, NIV was constantly successful and could be safely pushed further in case of severe hypercapnic acute respiratory decompensation of OHS.